Analisis numerik karakteristik intensitas suara gending Jawa - N. Finahari; G. Soebiyakto (Dinamika Teknik Mesin, 2017)
The use of Javanese Gending as music therapy is conducted by the method of stereo playback. With reference to that flow into the voice information left and right ears are different but ended in the same area, it is necessary to an understanding of the response mechanisms that emerged from each of the groove and the existence of interactions. Overview of acoustic parameter response interaction right brain hemisphere and the left brain are manifested in the form of a mathematical equation. This study aims to formulate sound characteristic of Javanese music in numerical form, as a sound source of the study. In this case, the numerical model obtained will be used as the excitation force vibration system that enters the auditory system.